Research of Youth Preferences in the Forms of Carrying Out Leisure - Sergey Petrovich Ivanenkov; Azhar Zhalelevna Kuszhanova (Управленческое консультирование)
The article presents the results of sociological research of the dynamics of the positions of youth during 2012- 2014 on the preferences given to it by various forms of carrying out leisure.